Reinwardtia, 75 years of endeavour investigating Indonesia’s botany and beyond - Sumadijaya, Alex; Agustiani, Esthi; Senjaya, Seni; Wulansari, Tri (Reinwardtia, 2025)
SUMADIJAYA, A., AGUSTIANI, E. L., SENJAYA, S. K. & WULANSARI, T. Y. I. 2025. Reinwardtia, 75 years ofendeavour investigating Indonesia’s botany and beyond. Reinwardtia 24(1): 137‒144. — Decades of publications in Reinwardtia reveal the dynamics and transition of botanical research in Indonesia. This synthesis delivers snapshots across third-quarter-century accumulation of plant and fungi knowledge, mostly in taxonomy, with a glimpse into ecology, ethnobotany, and others. Disparity of studies is prevalent for Angiosperms and taxa in Indonesia, particularly Java, Sumatra, and Sulawesi. Across decades, the transition of editors and authors delivers strong evidence of a scientific void and prolonged time to recover the vacuum. It also provides a sweet spot between decolonization while maintaining global participation.